Study on the association between maternal urinary phthalate metabolites and testicular steroid hormones in the cord blood in a Chinese population - Chen, Xi; Ma, Jing; Yu, Hao; Leng, Ling; Zhou, Qinghong; Sun, Zengrong; Tang, Naijun (Zhōnghuá yùfáng-yīxué zázhì, 2014)
The purposes of our study were to investigate the association between maternal urinary phthalate metabolites and the levels of inhibin B (INHB) and insulin-like factor 3 (INSL3) in the cord blood in a Chinese pregnant population. Maternal urine samples in the third trimester of pregnancy of 69 participants were collected and stored, and the samples of cord blood (10 ml) were collected at delivery between June 2011 and September 2012 in a comprehensive hospital of gynecology and obstetrics in Tianjin, China.Four phthalate metabolites, monomethyl phthalate (MMP), monoethyl phthalate (MEP), monobutyl phthalate (MBP), and mono-2-ethylhexyl phthalate (MEHP) were measured in the urine samples using liquid chromatography-tandem mass spectrometry. The levels of INHB, INSL3 in the cord blood were tested by ELISA. Associations of phthalate exposure with INHB and INSL3 levels were determined by spearman correlation and multiple regression model analysis. The median concentrations of observed metabolites in descending or